Lives and relationships : culture in transitions between social roles - Omi, Yasuhiro; Rodríguez, Lilian Patrices; Peralta-Gómez, María Claudia (Advances in cultural psychology., 2014)
This book brings to cultural psychology the focus on phenomenology of everyday life. Whether it is in the context of education, work, or exploration of life environments, the chapters in this book converge on the need to give attention to complex realities of everyday living. Thus, a description of pre-school organization in Japan would be in its form very different from school organization in Britain or Colombia--yet the realities of human beings acting in social roles are continuous around the world.